2014
DOI: 10.5455/jeim.180913.or.091
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cultured mesenchymal stem cells derived from bone marrow or peripheral blood of rats

Abstract: Objectives: Mesenchymal stem cells (MSC) are primarily isolated from bone marrow. Peripheral blood is also reported as an alternative source of MSC. This study compared MSC which were isolated and cultured from bone marrow and those from peripheral blood of rats. Methods: MSC from bone marrow and peripheral blood were harvested from 5 male Sprague Dawley rats. After isolation, the cells were grown on tissue culture plates with concentration of 10 7 cells per well. Observations were conducted to evaluate the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, our study is the first to report a positive effect on angiogenesis by CM from PB‐MSCs, because previous studies used CM from MSCs isolated from bone marrow (BM‐MSCs) or adipose tissues [4244]. It is also important to note that BM and adipose tissue, although more enriched in MSCs, are a more invasive source and, therefore, less accessible for regenerative therapy compared with PB as a source for MSCs [19, 27, 45]. PB‐MSCs have been demonstrated to express the same markers and to have similar differentiation potential compared with those derived from BM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study is the first to report a positive effect on angiogenesis by CM from PB‐MSCs, because previous studies used CM from MSCs isolated from bone marrow (BM‐MSCs) or adipose tissues [4244]. It is also important to note that BM and adipose tissue, although more enriched in MSCs, are a more invasive source and, therefore, less accessible for regenerative therapy compared with PB as a source for MSCs [19, 27, 45]. PB‐MSCs have been demonstrated to express the same markers and to have similar differentiation potential compared with those derived from BM.…”
Section: Discussionmentioning
confidence: 99%
“…Under the in vitro protocol, no PBMSCs were isolated from the non‐mobilized blood samples. Others have had more success, however, they used younger animals. The isolation of cells was performed in ex‐breeders, which are adult through to geriatric, and age related changes in stem cell differentiation, proliferation and metabolism are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Humans also show reduced CFUs with ageing and a recent study also showed an age relationship with CXCR4 dependent migration and hence the effect of antagonism of the CXCR4‐SDF1 axis may also reduce with age. Most of the studies looking at peripheral blood circulating stem cells and mobilization in animal models have used young immature animals, and therefore there may be merit in evaluating the role of age in mobilization potential. Although the rats were not ovariectomized, assessing mobilization in ex‐breeders is more relevant, as the likely target population for translation will be fractures in older patients and in those with osteoporosis where fracture healing is more likely to be impaired than in young individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of nucleus cells that were similar to fibroblast cells, their morphology was evaluated, while their attachment to the plastic culture plates was passaged 4-5 times. 19,20 Characterization of ADMSCs in the culture media was carried out by means of an immunocytochemical staining technique. Single cells derived from the trypsinization process were centrifuged.…”
Section: Methodsmentioning
confidence: 99%